2018
DOI: 10.18632/oncotarget.25087
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome based individualized therapy of refractory pediatric sarcomas: feasibility, tolerability and efficacy

Abstract: Survival rates of pediatric sarcoma patients stagnated during the last two decades, especially in adolescents and young adults (AYAs). Targeted therapies offer new options in refractory cases. Gene expression profiling provides a robust method to characterize the transcriptome of each patient’s tumor and guide the choice of therapy.Twenty patients with refractory pediatric sarcomas (age 8-35 years) were assessed with array profiling: ten had Ewing sarcoma, five osteosarcoma, and five soft tissue sarcoma. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…This study showed that patients treated with therapy targeting genetic alterations are likely to benefit. 55 In a study of 71 OGS samples from 66 adults and paediatric patients, next-generation sequencing (NGS) was used to identify potentially actionable mutations. Out of these 71 samples, 32 were from metastatic or recurrent lesions.…”
Section: Genomic Profiling Next-generation Sequencing and Target-basmentioning
confidence: 99%
“…This study showed that patients treated with therapy targeting genetic alterations are likely to benefit. 55 In a study of 71 OGS samples from 66 adults and paediatric patients, next-generation sequencing (NGS) was used to identify potentially actionable mutations. Out of these 71 samples, 32 were from metastatic or recurrent lesions.…”
Section: Genomic Profiling Next-generation Sequencing and Target-basmentioning
confidence: 99%
“…Previous study indicated that immune infiltration in tumor is prognostic for anticancer therapies [4,5]. Genomics and transcriptome based individualized therapy in sarcoma have shown a survival benefit [6]. The results of our analysis can potentially be correlated to the response of LMS and DDLPS to chemotherapy, targeted therapy, or immunotherapy, and can be used to develop biomarkers of therapeutic choice.…”
Section: Introductionmentioning
confidence: 84%
“…Tumor Mutational Burden And Microsatellite Status 6 Tumor mutational burden (TMB) was calculated from the total number of nonsynonymous somatic mutation using a published algorithm [14]. All autosomal microsatellite tracts containing 1-5 bp repeating subunits in length and comprising five or more repeats in GRCh37/hg19 were identified using MISA (http://pgrc.ipk-gatersleben.de/misa/misa.html) [15].…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%
“…Despite the lower prevalence of actionable mutations, targeted therapy gives pediatric oncologists further hope in the treatment of refractory or relapsed pediatric cancers. In a case-controlled study of nine pediatric patients with refractory sarcoma, targeted therapy resulted in improvement of the overall survival to 8.83 months versus 4.93 months, and improvement of the progression-free survival to 6.17 months versus 1.6 months in the control group [23]. However, because of a possible increase in the number of mutations and changes in the mutational spectrum, the importance of testing relapsed or metastatic rather primary tumors cannot be over-emphasized [24].…”
Section: Precision Applications In Childhood Cancermentioning
confidence: 99%